The Translation of Judgments - Poon Wai-Yee, Emily (Meta, 2006)
AbstractThis paper advocates the adoption of a plain language approach in the translation of judgments. The front-line objective is to gradually develop among legal practitioners the consciousness of using Chinese as a legal language, whether it is for judgment writing or for use as the trial language. While the pilot project on the translation of case law launched by the Subcommittee on the Translation of Case Precedents was a good attempt to boost the translation incentive, it exposed a number of problems in legal translation as yet unsolved. This paper explores potential solutions to these problems, including studying the syntactic differences between English and Chinese, the employment of common Chinese usages, and the application of legal knowledge, among others. This paper argues that legal bilingualism in courts will not be fully achieved if the problems of writing or understanding judgments persist.